Preferences and Biases in Educational Choices and Labour Market Expectations: Shrinking the Black Box of Gender. (30th January 2017) - Reuben, Ernesto; Wiswall, Matthew; Zafar, Basit
Abstract : Using an experiment to measure overconfidence and preferences for competitiveness and risk, this article investigates whether these measures explain gender differences in college major choices and expected future earnings. We find that individuals who are overconfident and overly competitive expect to earn significantly more. In addition, gender differences in overconfidence and competitiveness explain 18% of the gender gap in earnings expectations. These experimental measures explain as much of the gender gap in earnings expectations as a rich set of control variables. While expected earnings are related to college major choices, the experimental measures are not related with college major choice.